2019
DOI: 10.1002/anie.201812836
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecific Synthesis of α‐Hydroxy‐Cyclopropylboronates from Allylic Epoxides

Abstract: Herein, we report a catalytic and stereospecific method for the preparation of enantioenriched a-hydroxy cyclopropylboronates with control in four contiguous stereocenters. The reaction involves the borylation of readily available allylic epoxides using an inexpensive Cu(I) salt and a commercially available phosphine ligand. High diastereocontrol is achieved and different diastereomers can be selectively prepared. Functionalization of the carbon-boron bond provides access to different enantiomerically enriched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…The research group of Miura reported an asymmetric aminoboration of oxa‐ and azabicyclic alkenes with diboron reagents [B 2 pin 2 , Bpin‐Bdan (dan=1,8‐diaminonaphthalenyl)] and O ‐benzoyl‐hydroxylamines under copper catalysis while maintaining the bicyclic framework [83] . Very recently, Tortosa and co‐workers reported a couple of striking examples of the potentiality of copper‐boryl complexes in organic synthesis [84,85] . They discovered that aryl substituted vinylepoxides (such as A , Scheme 23) after initial regioselective carboboration to give intermediate B , undergo an intramolecular S N 2 type reaction to afford stereospecifically cyclopropylboronate D [84] .…”
Section: Diboron Compounds and Silaboranesmentioning
confidence: 99%
See 1 more Smart Citation
“…The research group of Miura reported an asymmetric aminoboration of oxa‐ and azabicyclic alkenes with diboron reagents [B 2 pin 2 , Bpin‐Bdan (dan=1,8‐diaminonaphthalenyl)] and O ‐benzoyl‐hydroxylamines under copper catalysis while maintaining the bicyclic framework [83] . Very recently, Tortosa and co‐workers reported a couple of striking examples of the potentiality of copper‐boryl complexes in organic synthesis [84,85] . They discovered that aryl substituted vinylepoxides (such as A , Scheme 23) after initial regioselective carboboration to give intermediate B , undergo an intramolecular S N 2 type reaction to afford stereospecifically cyclopropylboronate D [84] .…”
Section: Diboron Compounds and Silaboranesmentioning
confidence: 99%
“…Very recently, Tortosa and co‐workers reported a couple of striking examples of the potentiality of copper‐boryl complexes in organic synthesis [84,85] . They discovered that aryl substituted vinylepoxides (such as A , Scheme 23) after initial regioselective carboboration to give intermediate B , undergo an intramolecular S N 2 type reaction to afford stereospecifically cyclopropylboronate D [84] . Alternatively, if intermediate B is intercepted by protonolysis before cyclization, the corresponding epoxy boronate F undergoes base‐promoted β‐oxygen elimination to give a formal reduction product (Scheme 24).…”
Section: Diboron Compounds and Silaboranesmentioning
confidence: 99%
“…Recently, we used vinyl epoxides to prepare cyclopropylboronates B using a readily available copper(I) catalyst. 11 The catalytic cycle involved the formation of organocopper A from a vinyl epoxide and a copper-boryl complex, followed by an intramolecular SN2-type reaction to provide B. We hypothesized that, in the presence of a proton source such as MeOH, 12 intermediate A would be intercepted before cyclization to afford epoxy boronate C. This intermediate could undergo a basepromoted b-oxygen elimination to give the formal reduction product.…”
Section: Scheme 1 Reduction Of Vinyl Epoxidesmentioning
confidence: 99%
“…To test our hypothesis, we selected vinyl epoxide 1a, previously used in our cyclopropane synthesis. 11,14 This starting point was of particular interest given that the 1,4-reduction of vinyl epoxides with a simple aryl group in the double bond is virtually unknown in the literature. 15 Gratifyingly, with similar conditions to those used for the cyclopropanes, in the presence of a proton source, we observed the formation of allylic alcohol 2a as a single E-isomer (Table 1, entry 1).…”
Section: Scheme 1 Reduction Of Vinyl Epoxidesmentioning
confidence: 99%
See 1 more Smart Citation